1995
DOI: 10.1164/ajrccm.152.6.8520735
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of immediate hypersensitivity and airway hyperresponsiveness by IgE-positive B cells.

Abstract: The role of allergen-specific sIgE+ B cells in the development of airway hyperresponsiveness to electrical field stimulation was examined in a murine model of allergic sensitization. Ovalbumin (OVA)-specific B cells (OVA+) were isolated from mice that were sensitized to aerosolized OVA. The OVA+ B cell population was shown to be distinct from the remaining, non-OVA-responsive B cells (OVA-). There was a high frequency of sIgE+ B cells and a low frequency of sIgG+ B cells in the OVA+ population compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…They have shown that BHR, measured by an ex vivo assay, and eosinophilic inflammation after OVA challenge can be passively transferred to naive recipients by IgE or IgE ϩ B cells from animals sensitized to OVA only by inhalation (18). IgE-independent mechanisms involving the generation of allergen-specific CD8 ϩ cells also may participate in pathogenesis in this model (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have shown that BHR, measured by an ex vivo assay, and eosinophilic inflammation after OVA challenge can be passively transferred to naive recipients by IgE or IgE ϩ B cells from animals sensitized to OVA only by inhalation (18). IgE-independent mechanisms involving the generation of allergen-specific CD8 ϩ cells also may participate in pathogenesis in this model (38).…”
Section: Discussionmentioning
confidence: 99%
“…Nebulized ovalbumin (OVA) has been used to elicit specific IgE responses and bronchial hypersensitivity in mice (17). The passive transfer of IgE ϩ B cells has been shown to confer OVA-inducible BHR in this model (18). Mice bred for high levels of IgE production have been reported to manifest both greater BHR and more eosinophil infiltration in the respiratory epithelium after OVA sensitization and challenge than control animals (19).…”
mentioning
confidence: 99%
“…Previous studies concerning B cells in allergic disease have concluded that B cells play no role in the development of allergic disease as characterized by inflammation, eosinophilia, and AHR [17], [18]. Other studies have suggested that the contribution of B cells is primarily via IgE [19], [20]. Still other studies which support a role for B cells in allergic lung disease did not directly address the mechanism by which B cells contribute to allergic disease [21], [22].…”
Section: Introductionmentioning
confidence: 99%
“…For example, mice lacking B cells or IgE (Mehlop et al, 1997) develop AHR and eosinophilia indistinguishable from control animals. However, transfer of IgE from OVA-sensitized into naïve animals can induce the development of eosinophilia and AHR on exposure to OVA, demonstrating that allergen-specific IgE is sufficient to induce an asthma-like phenotype (Lack et al, 1995), but may not be required.…”
Section: Assessment and Characteristics Of The Experimental Allergic mentioning
confidence: 99%